شركة موانج تاي تكافل بتايلاند : دراسة فقهية تقويمية - Noormasitah Binti Johan
This research aims to investigate the Takaful (Islamic Insurance) services and applications of the Muang Thai Takaful Company of Thailand and examine the legitimacy of those sevices from an Islamic juristic perspective. It identifies the concept of Takaful and its legality in Islam, and describes its current reality in Thailand. Furthermore, it examines Muang Thai Takaful Company in terms of its foundation and development, as well as its executive bodies and mechanisms. Moreover, it presents the principles of Takaful upon which the company provides its services, products and contracts, and evaluates them from an Islamic juristic point of view. This study makes use of the inductive and analytical methods, and employs the empirical method through interviews conducted with company officials and staff members. The results for this study find that the services and applications of Muang Thai Takaful are mostly compatible with the Islamic Shari'ah, and recommendations are proposed in order to rectify minor incompatible services and applications.